DESKRIPSI PELAKSANAAN PEMBELAJARAN MATEMATIKA MENGGUNAKAN GOOGLE CLASSROOM OLEH GURU DI KELAS X SMA - Fridolin Wilton Arke; Agung Hartoyo; Asep Nursangaji (Jurnal AlphaEuclidEdu, 2022)
The purpose of this study was to find out and describe how the implementation of mathematics learning using google classroom was carried out by the teacher in class X MIA SMAN 1 Jongkong. The subjects of this study came from class X MIA which consisted of 24 students. This research method is descriptive quantitative. Collecting data from interviews, questionnaires, learning outcomes tests by teachers with the material of linear equations and inequalities of one variable containing absolute values, as well as documentation. The research description shows that the implementation of mathematics learning using google classroom by the teacher gets a percentage of 59.37% and is in the sufficient category, the learning plan assessment by linking the TPACK (Technological Pedagogical and Content Knowledge) values gets a percentage of 57.14% and is in the medium category, the presence of students in the implementation of learning mathematics using google classroom gets a percentage of 100% and is in a good category, the percentage of student learning outcomes in learning mathematics using google classroom is 82.67% and is in the very good category, student responses get a percentage of 74.79% and are in the category high, the teacher's response gets a percentage of 71.25% and is in the high category.